Identification of genes involved in enhanced membrane vesicle formation in Pseudomonas aeruginosa biofilms: surface sensing facilitates vesiculation - Kanno, Mizuki; Shiota, Takuya; Ueno, So; Takahara, Minato; Haneda, Keisuke; Tahara, Yuhei O.; Shintani, Masaki; Nakao, Ryoma; Miyata, Makoto; Kimbara, Kazuhide; Futamata, Hiroyuki; Tashiro, Yosuke (Frontiers in Microbiology, 2023)
Membrane vesicles (MVs) are small spherical structures (20-400 nm) produced by most bacteria and have important biological functions including toxin delivery, signal transfer, biofilm formation, and immunomodulation of the host. Although MV formation is enhanced in biofilms of a wide range of bacterial species, the underlying mechanisms are not fully understood. An opportunistic pathogen, P. aeruginosa, causes chronic infections that can be difficult to treat due to biofilm formation. Since MVs are abundant in biofilms, can transport virulence factors to the host, and have inflammationinducing functions, the mechanisms of enhanced MV formation in biofilms needs to be elucidated to effectively treat infections. In this study, we evaluated the characteristics of MVs in P. aeruginosa PAO1 biofilms, and identified factors that contribute to enhanced MV formation. Vesiculation was significantly enhanced in the static culture; MVs were connected to filamentous substances in the biofilm, and separation between the outer and inner membranes and curvature of the membrane were observed in biofilm cells. By screening a transposon mutant library (8,023 mutants) for alterations in MV formation in biofilms, 66 mutants were identified as low-vesiculation strains (2/3 decrease relative to wild type), whereas no mutant was obtained that produced more MVs (2-fold increase). Some transposons were inserted into genes related to biofilm formation, including flagellar motility (flg, fli, mot) and extracellular polysaccharide synthesis (psl). ΔpelAΔpslA, which does not synthesize the extracellular polysaccharides Pel and Psl, showed reduced MV production in biofilms but not in planktonic conditions, suggesting that enhanced vesiculation is closely related to the synthesis of biofilm matrices in P. aeruginosa. Additionally, we found that blebbing occurred during bacterial attachment. Our findings indicate that biofilm-related factors are closely involved in enhanced MV formation in biofilms and that surface sensing facilitates vesiculation. Furthermore, this work expands the understanding of the infection strategy in P. aeruginosa biofilms.